2010
DOI: 10.1002/mnfr.200900043
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and thermal stability of Lep w 1, the major allergen of whiff

Abstract: Whiff (Lepidorhombus whiffiagonis) is a fish frequently consumed in Spain. Lep w 1, its major allergen, is a calcium-binding beta-parvalbumin. The resistance of Lep w 1 to heat denaturation and to digestion were studied by circular dichroism spectroscopy and by in vitro gastric digestion systems. Purified Lep w 1 was thermally stable up to 65 degrees C at neutral pH. Calcium depletion resulted in a change of its structure as determined by circular dichroism spectroscopy. A partial loss of structure was also ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…These proteins are thermostable proteins that present high stability towards food processing and enzymatic digestion. 33 In the current study, it was also found that hake parvalbumins present a remarkable stability to HP treatments and even showed an increase in their intensity after applying pressure ≥ 430 MPa (Figure 3s). These results might be used for the development of further allergenic studies using different hake HP treatments and sera from parvalbumin allergic patients.…”
Section: Discussionsupporting
confidence: 68%
“…These proteins are thermostable proteins that present high stability towards food processing and enzymatic digestion. 33 In the current study, it was also found that hake parvalbumins present a remarkable stability to HP treatments and even showed an increase in their intensity after applying pressure ≥ 430 MPa (Figure 3s). These results might be used for the development of further allergenic studies using different hake HP treatments and sera from parvalbumin allergic patients.…”
Section: Discussionsupporting
confidence: 68%
“… 14 Interestingly, calcium depletion reduced IgE binding to parvalbumin in most patient sera. 14 Fish parvalbumin is thermally stable 15 and maintains its allergenic activity and antigenicity even under acidic conditions and after pepsinolysis. 13 , 16 Short burst swimming in fish is powered by white muscles, which have a higher parvalbumin content than the dark muscles that drives continuous stroke.…”
Section: Fish Allergens and Cross-reactivitymentioning
confidence: 99%
“…They are low molecular weight proteins (10–12 kDa) that are highly stable (e.g. upon heating, enzymatic digestion) and bind bivalent ions such as calcium or magnesium [ 98 ]. Parvalbumins belong to the ‘EF hand’-protein family as the ion-binding is affected by structural motifs, which are characteristic for this family [ 99 ].…”
Section: Fish Allergensmentioning
confidence: 99%